Touchpoints : creating powerful leadership connections in the smallest of moments - Conant, Douglas R., 1951- (Warren Bennis signature series., 2011)
"A fresh, effective, and enduring way to lead starting with your next interaction. Most leaders feel the inevitable interruptions in their jam-packed days are troublesome. But in TouchPoints, Conant and Norgaard argue that these--and every point of contact with other people--are overlooked opportunities for leaders to increase their impact and promote their organization's strategy and values. Through previously untold stories from Conant's tenure as CEO of Campbell Soup Company and Norgaard's vast consulting experience, the authors show that a leader's impact and legacy are built through hundreds, even thousands, of interactive moments in time. The good news is that anyone can develop "TouchPoint" mastery by focusing on four essential components: head, heart, hands and touch. Promotes a new intuitive model of rational, active, and wise leadership practices. Shows how the authenticity of a leader is tested during every informal interaction, every day. Introduces four integrated commitments that are foundational to mastering the TouchPoints: the commitment to inquiry, reflection, practice, and continuous improvement. Compelling and transformative, this book shows how TouchPoint mastery can turn otherwise ordinary moments into powerful opportunities for influence with lasting impact--one TouchPoint at a time."--Provided by publisher